Formal Specification Based Automatic Test Generation for Embedded Network Systems - Eun Hye Choi; Hideaki Nishihara; Takahiro Ando; Nguyen Van Tang; Masahiro Aoki; Keiichi Yoshisaka; Osamu Mizuno; Hitoshi Ohsaki (Journal of Applied Mathematics)
Embedded systems have become increasingly connected and communicate with each other, forming large-scaled and complicated network systems. To make their design and testing more reliable and robust, this paper proposes a formal specification language called SENS and a SENS-based automatic test generation tool called TGSENS. Our approach is summarized as follows: (1) A user describes requirements of target embedded network systems by logical property-based constraints using SENS. (2) Given SENS specifications, test cases are automatically generated using a SAT-based solver. Filtering mechanisms to select efficient test cases are also available in our tool. (3) In addition, given a testing goal by the user, test sequences are automatically extracted from exhaustive test cases. We’ve implemented our approach and conducted several experiments on practical case studies. Through the experiments, we confirmed the efficiency of our approach in design and test generation of real embedded air-conditioning network systems.